Budidaya ikan mas (Cyprinus carpio) sistem akuaponik dengan padat penebaran berbeda - Darwis, Darwis; Mudeng, Joppy D.; Londong, Sammy N.J. (Universitas Sam Ratulangi, 2019)
This research aimed to determine the stocking density that support the best growth and survival rate of carp cultivated in aquaponic systems, and to study the water quality of carp culture with different stocking densities in aquaponic systems. The study used 12 aquaria measuring 40x40x40 cm each (water volume of 50 liters). The experimental fish are carp (Cyprinus carpio) weighing in average of 3.5 g/individual.Â The fish were cultivated with different stocking densities as treatment, including A = 4; B = 7; C = 10 and D = 13 individuals/aquarium.Â The fish were fed with pellet at 5%/body weight/day with a feeding frequency of two times a day. The study was conducted for 4 weeks. Data consisting of daily growth, survival and water quality parameters (temperature, pH, dissolved oxygen, ammonia, nitrite and nitrate) were measured once a week. The data obtained were analyzed by ANOVA. The results of the study showed that the difference in stocking density had no significant effect on the growth and survival of carp. Â Water quality was in a reasonable range to support the growth and survival of carp cultivated with aquaponic systems.Keywords: cultivation, carp, aquaponics, stocking density, growth